2021
DOI: 10.1002/jhbp.1017
|View full text |Cite
|
Sign up to set email alerts
|

Detrimental effect of intraoperative hypothermia on pancreatic fistula after pancreaticoduodenectomy: A single‐centre retrospective study

Abstract: Background Although perioperative hypothermia was found to be associated with gastrointestinal anastomotic leakage in preclinical studies, its association with postoperative pancreatic fistula (POPF) following pancreaticoduodenectomy was never evaluated. We investigated the association between intraoperative hypothermia and clinically relevant (CR)‐POPF following pancreaticoduodenectomy. Methods We retrospectively reviewed 2163 consecutive patients who underwent pancreaticoduodenectomy during 2007‐2019. Based … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…The complicated surgery affects both the internal organs of the abdominal cavity and the body's heat metabolism, resulting in more heat loss during the operation than in other surgeries, and the proportion of malignant tumours is high. Patients undergoing such surgery are at high risk of hypothermia [ 3 ]. Studies have shown that intraoperative hypothermia can lead to complications such as increased intraoperative blood loss, prolonged anaesthesia resuscitation time, increased postanaesthesia care unit or intensive care unit stay, a 20 % longer hospital stay and postoperative wound infection, which can lead to ventricular arrhythmia, ventricular fibrillation and even cardiac arrest or death [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…The complicated surgery affects both the internal organs of the abdominal cavity and the body's heat metabolism, resulting in more heat loss during the operation than in other surgeries, and the proportion of malignant tumours is high. Patients undergoing such surgery are at high risk of hypothermia [ 3 ]. Studies have shown that intraoperative hypothermia can lead to complications such as increased intraoperative blood loss, prolonged anaesthesia resuscitation time, increased postanaesthesia care unit or intensive care unit stay, a 20 % longer hospital stay and postoperative wound infection, which can lead to ventricular arrhythmia, ventricular fibrillation and even cardiac arrest or death [ 4 ].…”
Section: Introductionmentioning
confidence: 99%